Miconia renatogoldenbergii (Miconieae, Melastomataceae), a new species from savanna enclaves in southern Amazonia, Brazil - Meirelles, Julia; Bacci, Lucas F. (Phytotaxa, 2017)
A new species of Miconia section Miconia, subsection Seriatiflorae from the Brazilian Amazonian region is described. Miconia renatogoldenbergii has a wide distribution in areas of savanna and forest understory in the states of Pará, Mato Grosso and Rondônia. It is similar to M. punctata as both species have chartaceous leaves with rusty lepidote indument on the abaxial surface. The new species can be distinguished by its mucronate leaf apex, a thyrse with short scorpioid branches, and subulate anthers, with round apex, dehiscent through an apical pore and with cordate connective appendages.